(untitled) (Al-Qamar, 2020)
The present paper intends to explore the history and nature of Western ideas regarding the personality and character of the Prophet in the Middle Ages. It leads to the conclusion that, with a few exceptions, the attitude of the Romans towards Islam and Prophet of Islam has been aggressive and hostile, and the contribution of Roman thought and civilization in the foundations of Europe needs no explanation. Thus, the West inherited the enmity and opposition of the Prophet of Islam. It is clear from the research of Muslim scholars as well as many non-Muslim Western scholars that Western ideas about the Prophet at the time referred were based on prejudice and opposition. Every evil that one could imagine was attributed to the Prophet. Watt has rightly said that: “of all the world’s great men none has been so much maligned as Muhammad.”